The evolution of the importance of the true and fair view (TFV) principle. The case of Poland - Piechocka-Kałużna, Agnieszka (Ewolucja znaczenia zasady wiernego i rzetelnego obrazu na przykładzie Polski, 2018)
The aim of this paper is to analyse matters of truth, which is inherent issue of accounting (and therefore in reporting, as its part), which is reflected in the true and fair principle (TFV). The paper demonstrates the essence of the TFV principle and the evolution of its role and place among the set of qualitative characteristics of financial statements. After examining the changes in the development of the perception of TFV the paper makes an appraisal, gives the author’s comments and contribution by providing direct implications for regulators and the setters of standards. With respect to typical limitations regarding behavioural studies, the paper provides practical as well as social implications about understanding of the TFV concept and its effect on both the preparers and users of financial statement
Financial Sciences. Nauki o Finansach, 2018, vol. 23, no. 4, s. 89-101
Keywords: true and fair view concept (TFV); truth in accounting; truth in reporting; qualitycharacteristics of financial statements